Inequality in investment and access to education for children: An analysis from the Vietnam household living standards survey - Nguyen Thanh, Hien (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The study examines household expenses on education in Vietnam to assess the inequality in investment and access to education for children from the perspective of inequality of opportunity. The study uses descriptive statistics, t-tests, and analysis of variance to explore the structure of expenditure on education and compare the differences in schooling costs of students with different socioeconomic backgrounds using the 2018 Vietnam Household Living Standards Survey data. The study results show that in the expense structure, school-related expenses such as extra classes, uniforms, and school contributions are factors that can increase the economic burden. Rural students, ethnic minorities, and those in less economically developed areas receive less educational support and investment, primarily due to school-related expenses rather than tuition fees. Disparities in educational expenses among households can exacerbate inequality in access to education among different groups of children and undermine the effectiveness of educational policies, such as tuition fee support and exemption. To mitigate educational inequality, in addition to tuition fee support and exemption, it is necessary to design targeted policies to support students with specific economic conditions in covering their educational expenses.